Aplicaciones pedagógicas del extractor de aceites esenciales por arrastre de vapor en procesos de transformación agroindustrial. - De la Cruz Burbano, Jonathan Esteban (2022)
The objective of this research is the pedagogical application of the essential oil extracted by steam dragging in agro-industrial transformation processes. Manuals of operation, maintenance and safety of the personnel were elaborated, with the purpose of promoting the optimal conditions for the installation, use, and maintenance of the equipment, this was used in the Bromatology research laboratory of the Agroindustrial Engineering Career of the Technical University of Cotopaxi. In the technological and scientific development, during the construction of the investigation, the correct operation, assembly, and use of the extractor were demonstrated, with the purpose of responding to eventual situations that may arise during its use. For the development of the manual, the following investigations were used: bibliographical, experimental, and descriptive, this will allow identifying the characteristics, parameters, and requirements, specifying the generalities of the mode of operation and the different types of maintenance that the equipment requires. Finally, a demonstrative practice was carried out with three types of plants (tzintzo, lemon verbena, and eucalyptus) in order to demonstrate the highest yield percentage of extraction per Kg of plant matter, resulting in the largest amount of essential oil extracted from the plant of fresh eucalyptus with the amount of 4,93 ml.